2006
DOI: 10.3928/1081-597x-20061001-09
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Ablation Approach to the Correction of Mixed Astigmatism

Abstract: PURPOSE: To evaluate the safety, efficacy, and stability of LASIK, using positive cylinder and negative sphere nomograms in sequence (sequential ablation) to correct mixed astigmatism. METHODS: This prospective study included 40 eyes of 20 patients with mixed astigmatism. Patients underwent bilateral sequential ablation LASIK using the Technolas 217 excimer laser (Bausch & Lomb Surgical, Rochester, NY). The main outcome measures, uncorrected visual acuity (UCVA) and best spectacle-corrected visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…All eyes had a mean spherical equivalent refraction within ±0.50 D of the intended correction and the residual astigmatism was ≤0.50 D in all eyes treated with the WaveLight Allegretto Wave 400 Hz in the study by Stonecipher et al (1). Pinelli et al (2) reported that 80% of patients (n = 32) treated with the Technolas 217 excimer laser had no residual astigmatism (≤0.50 D) and the remaining 20% (n = 8) had residual astigmatism between 0.50 D and 1.00 D. We found that at postoperative month 3, one eye in the WaveLight group and 3 eyes in the Technolas group had no residual astigmatism (P = 0.213). Spherical equivalent values were -0.38 ± 0.73 D in the WaveLight group and -0.33 ± 0.20 D in the Technolas group (P = 0.562).…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…All eyes had a mean spherical equivalent refraction within ±0.50 D of the intended correction and the residual astigmatism was ≤0.50 D in all eyes treated with the WaveLight Allegretto Wave 400 Hz in the study by Stonecipher et al (1). Pinelli et al (2) reported that 80% of patients (n = 32) treated with the Technolas 217 excimer laser had no residual astigmatism (≤0.50 D) and the remaining 20% (n = 8) had residual astigmatism between 0.50 D and 1.00 D. We found that at postoperative month 3, one eye in the WaveLight group and 3 eyes in the Technolas group had no residual astigmatism (P = 0.213). Spherical equivalent values were -0.38 ± 0.73 D in the WaveLight group and -0.33 ± 0.20 D in the Technolas group (P = 0.562).…”
mentioning
confidence: 89%
“…Different approaches have been reported: negative-cylinder nomogram, positivecylinder nomogram, cross-cylinder technique, bitoric ablation, and sequential ablation. The common goal in the treatment of mixed astigmatism is to remove the minimum amount of tissue while achieving good visual results (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations